AB0474 Changes in T and B Lymphocyte Subsets with Tofacitinib do not Translate from Nonclinical Species to Humans. (10th June 2014) - Ball, D.J.; Kawabata, T.T.; Vogel, W.M.; Riese, R.J.; Krishnaswami, S.; Lamba, M.; Brown, M.J.; Zwillich, S.H.
Abstract : Background: Tofacitinib is an oral Janus kinase (JAK) inhibitor for the treatment of rheumatoid arthritis (RA). Cytokines involved in lymphocyte development, function and homeostasis (e.g., interleukin (IL)-2, -4, -7, -15, -21) signal through JAK. Repeat dose toxicology studies were conducted in rats and monkeys to support clinical development of tofacitinib. Objectives: The objective of the nonclinical studies was to determine the potential toxicity of tofacitinib with a focus on the effects on lymphocyte subsets. Based on the results from these nonclinical studies, Phase 2 studies with RA patients included lymphocyte subset monitoring. Methods: Absolute counts of total T cells (CD3+), CD4+ T cells, CD8+ T cells, B cells and natural killer (NK) cells were monitored in peripheral blood samples by flow cytometry. Changes from baseline values and changes relative to the vehicle/placebo treated groups were used to identify tofacitinib treatment related changes. Results: Tofacitinib treatment decreased all subsets in rats (6-month study) whereas only T and NK cells were decreased in monkeys (4- and 39-week studies). In RA patients (6 and 24 weeks of exposure), NK cell counts decreased and B cell counts increased. There were transient increases in T cell counts after 2 weeks of treatment. However, at the end of studies, counts were variable but near baseline levels (Table 1 ). Conclusions: The differences in directionality and magnitude of change, across different lymphocyte subsets, demonstrate that T cell generation and/or homeostasis is more sensitive to tofacitinib in monkeys than in humans. Based on the observed translational differences, any further studies to understand tofacitinib mechanism of action on lymphocyte subset and immune function should be conducted using human subjects rather than nonclinical species. Disclosure of Interest: D. Ball Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Kawabata Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, W. Vogel Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. Riese Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Krishnaswami Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, M. Lamba Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, M. Brown Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Zwillich Shareholder of: Pfizer Inc, Employee of: Pfizer Inc DOI: 10.1136/annrheumdis-2014-eular.2276